2020
DOI: 10.1080/12265934.2020.1803107
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impact on city and region: what’s next after lockdown?

Abstract: COVID-19 is unique in that it is spread through everyday contact with other people. Therefore, social protective measures, beyond medical protective measures, such as social distancing, lockdowns, border closures, and human tracing are initiated to control the spread of COVID-19. Such responses have produced secondary issues such as drastic changes in people's way of life and work, housing instability, economic shock, and privacy issues. This paper examines the four domains of urban and regional issues related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 23 publications
0
39
0
3
Order By: Relevance
“…Abou El-Magd and Zanaty ( 2020 ) used multi-data sensors and found that short-term lockdown had a significant impact on air quality and observed great reduction of carbon emissions from transportation, industrial, and human activities in Egypt. Another study was conducted by Kang et al ( 2020 ) in which the researcher studied secondary impact of COVID-19 on people’s way of life and work, housing instability, economic shock, and privacy in urban regions.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Abou El-Magd and Zanaty ( 2020 ) used multi-data sensors and found that short-term lockdown had a significant impact on air quality and observed great reduction of carbon emissions from transportation, industrial, and human activities in Egypt. Another study was conducted by Kang et al ( 2020 ) in which the researcher studied secondary impact of COVID-19 on people’s way of life and work, housing instability, economic shock, and privacy in urban regions.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…In the health professionals’ training, we know the restrictions that this has mean for teaching, but still know little of its effects, although there already are studies about this aspect in several countries of Europe [ 5 , 13 , 23 , 45 , 46 ], North America [ 24 ] and Asia [ 14 , 18 , 21 , 47 ], there are no evidences in this respect in Latin-America. Nor is there psychometric evidence backing up the instruments that have been employed up to date, or their suitability for an atypical formation context, such as the Emergency Remote Teaching [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a comparative perspective, South Korea appeared to adapt to the pandemic, while Italy and the United States struggled to address the spread. Kang et al [19] note South Korea's experience with previous viral outbreaks and their resilience planning by having pandemic plans, Though it is far too early to tell just how significant these trends may be, the potential impact of large-scale commercial dispersion on urban centers could be considerable. Millions of businesses rely on the daily patronage of office workers, as well as residents and tourists drawn to the urban core to access employment and entertainment opportunities.…”
Section: Scenario Planning Resilience Strategies and Their Integration Into Public Health Planningmentioning
confidence: 99%
“…From a comparative perspective, South Korea appeared to adapt to the pandemic, while Italy and the United States struggled to address the spread. Kang et al [19] note South Korea's experience with previous viral outbreaks and their resilience planning by having pandemic plans, health facilities, personal protective gear (PPE) stockpiles, and smart technology for contact tracing. Additionally, they argue that South Korea's community health centers played an integral role in COVID-19 screening and mitigation.…”
Section: Scenario Planning Resilience Strategies and Their Integration Into Public Health Planningmentioning
confidence: 99%